Bringing Total Quality Improvement into the College Classroom - Hansen, W. Lee (My University, 1993)
This paper describes a recent effort to infuse the Total Quality Improvement (TQI) approach, popularized by Deming and others, into an upper-division, junior-senior economics course at the University of Wisconsin-Madison. The process of infusing TQI into instruction has received relatively little attention. Most efforts to bring TQI into higher education focus on improving administrative operations and establishing courses and programs for students to learn how to apply TQI in their future jobs. The challenge is in using TQI to help students realize their potential for learning in traditional courses.